EVALUATION OF THE BIOACTIVITY AND ANTIBACTERIAL PROPERTIES OF TI6AL4V COATED WITH SERICIN AND GRAPHENE OXIDE - Keily, Christina
Ti6Al4V is a material commonly used as a bone implant due to its mechanical properties that are biocompatible with bone tissue. However, Ti6Al4V still has limitations in its osseointegration capability and carries a risk of microorganism infection due to biofilm formation on its surface. Surface modification of Ti6Al4V is one solution to address these issues. This study focuses on coating Ti6Al4V with sericin (SS) and a sericin-graphene oxide (SS/GO) mixture using tannic acid as a coupling agent because these can support osseointegration and enhance antibacterial properties. The aim of this coating is to improve the bioactivity of apatite formation as an initial indication of osseointegration capability and to enhance the antibacterial properties of Ti6Al4V. Sericin extraction was carried out using the high temperature high pressure (HTHP) method. Ti6Al4V was coated with SS and SS/GO for 24 and 48 hours, respectively. SEM images showed that the Ti6Al4V surface with the SS layer had a relatively smooth morphology, while coating with SS/GO resulted in a surface with GO agglomeration clusters. EDS mapping revealed the distribution of carbon, oxygen, and nitrogen elements in the SS and SS/GO layers. Bioactivity evaluation was conducted by incubating the samples in simulated body fluid for 14 days to induce apatite nucleation. Morphological analysis and the Ca/P ratio of the formed calcium phosphate indicated an increase in the bioactivity of Ti6Al4V coated with SS and SS/GO. Antibacterial evaluation against Staphylococcus aureus using the total plate count method showed a bacterial colony reduction of up to 83.89% for the SS coating with a deposition duration of 48 hours and 82.46% for the SS/GO coating with a deposition duration of 48 hours. Ti6Al4V coated with SS/GO for 48 hours showed the best potential as a bone implant candidate based on the increased bioactivity and antibacterial properties.